Structural basis of light-induced redox regulation in the Calvin-Benson cycle in cyanobacteria - McFarlane,C; Shah,N; Kabasakal,B; Echeverria,B; Cotton,C; Bubeck,D; Murray,J (Proceedings of the National Academy of Sciences of USA, 2019)
Plants, algae, and cyanobacteria fix carbon dioxide to organic carbon with the Calvin-Benson (CB) cycle. Phosphoribulokinase (PRK) and glyceraldehyde 3 phosphate dehydrogenase (GAPDH) are essential Calvin-Benson cycle enzymes that control substrate availability for the carboxylation enzyme Rubisco. PRK consumes ATP to produce the Rubisco substrate ribulose bisphosphate (RuBP). GAPDH catalyses the reduction step of the CB cycle with NADPH to produce the sugar, glyceraldehyde 3-phosphate (GAP), which is used for regeneration of RuBP and is the main exit point of the cycle. GAPDH and PRK are co-regulated by the redox state of a conditionally disordered protein CP12, which forms a ternary complex with both enzymes. However, the structural basis of Calvin-Benson cycle regulation by CP12 is unknown. Here we show how CP12 modulates the activity of both GAPDH and PRK. Using thermophilic cyanobacterial homologues, we solve crystal structures of GAPDH with different cofactors and CP12 bound, and the ternary GAPDH-CP12-PRK complex by electron cryo-microscopy, we reveal that formation of the N-terminal disulfide pre-orders CP12 prior to binding the PRK active site, which is resolved in complex with CP12. We find that CP12 binding to GAPDH influences substrate accessibility of all GAPDH active sites in the binary and ternary inhibited complexes. Our structural and biochemical data explain how CP12 integrates responses from both redox state and nicotinamide dinucleotide availability to regulate carbon fixation.